PENGARUH FORTIFIKASI BESI TERHADAP SIFAT ANTIBAKTERI SUSU FERMENTASI SINBIOTIK - , EUIS NURDIYAWATI; , Siti Helmyati, DCN, M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Iron deficiency anemia is one of the major nutritional problems in Indonesia. Iron fortification is one of the most effective and sustainable strategies in population. Iron fortification in fermented milk can increase intake of iron. Iron fortification contradictively, has negative effect on gut microbiota balance. Unabsorbed iron can increase the growth of pathogenic bacteria because iron is required for their growth. The type of fortificant have greatly affect iron absorption in the intestine. Probiotic can inhibit growth of pathogen and prevent human from gastrointestinal problem. As a local probiotic that being developed, Lactobacillus plantarum Dad 13 has proven provide many benefits for health. Fructooligosaccharide (FOS) can support the growth of comensal bacteria in gut by provide selective substrates for itâs growth. Objective : This study aimed to determine the effect of iron fortification (NaFeEDTA and FeSO4) on antibacterial activity of synbiotic fermented milk. Method : The antibacterial activity test was performed using the disc diffusion method. Paper discs were soaked in synbiotic fermented milk fortified with Fe (NaFeEDTA and FeSO4) or control (unfortified synbiotic fermented milk) then put on Nutrient Agar medium that was inoculated with Escherichia coli. The ability of inhibition was shown by the formation of clear zone around the paper disc and measured in diameter (mm), including the diameter of the paper disc. Results : Synbiotic fermented milk fortified with iron (either NaFeEDTA or FeSO4) has antibacterial activity against Escherichia coli with diameter of clear zone were 6.53 mm and 12.3 mm, respectively (p=0.05). Compared to control (10.73 mm), synbiotic fermented milk fortified with FeSO4 had similar antibacterial activity (p>0.05). Compared to control (10.73 mm), synbiotic fermented milk fortified with NaFeEDTA had different antibacterial activity (p=0.05). Conclusions : The kind of iron fortification compound affect the antibacterial activity of synbiotic fermented milk. In vitro, synbiotic fermented milk fortified with NaFeEDTA and FeSO4 had different antibacterial activity against Escherichia coli.